Intellectual property rights and detached human body parts. - Pila, J (2014)
This paper responds to an invitation by the editors to consider whether the intellectual property (IP) regime suggests an appropriate model for protecting interests in detached human body parts. It begins by outlining the extent of existing IP protection for body parts in Europe, and the relevant strengths and weaknesses of the patent system in that regard. It then considers two further species of IP right of less obvious relevance. The first are the statutory rights of ownership conferred by domestic UK law in respect of employee inventions, and the second are the economic and moral rights recognised by European and international law in respect of authorial works. In the argument made, both of these species of IP right may suggest more appropriate models of sui generis protection for detached human body parts than patent rights because of their capacity better to accommodate the relevant public and private interests in respect of the same.